PENERAPAN METODE DRILL UNTUK MENINGKATKAN KEMAMPUAN BINA DRI ANAK TUNA GRAHITA SEDANG KELAS II DISLB - FEBRI HARYATI, ANGGRAENI (Jurnal Pendidikan Khusus, 2017)
ABSTRACT The essence of self-improvement abilities is defined as the abilities that a child has after practicing a self-development program. The ability to practice merupkan one of the goals that need to be achieved in the learning process so that in practice teachers must be Creative, innovative and imaginative in order to improve the ability of children with moderate disabilities. The purpose of this study is to explain the application of Drill method to improve the ability of self-development of the mentally disabled children is the subject of this study of children with grade 2 Grade who are 6 students who have barriers of self-development ability.  This research method used pre-experimental quantitative research using Pre test and post test group design. Where is the initial treatment before the O2 intervention is provided after treatment and data collection techniques using the Test method and documentation. Technique of data analysis yan in use is sign test (sign test) Zh 2,05 with Zt 0,361. The result is an improvement for the ability of self-educated children who are tuna grahita are wearing school batik clothes, wearing pants, wearing shoes, wearing powder and taking care of 2nd grade hair In SLB Tunas Kasih Surabaya .   Keywords: drill method, improve the ability of self-esteem